HUBUNGAN KEPUASAN PELAYANAN ANTENATAL CARE DENGAN FREKUENSI KUNJUNGAN IBU HAMIL DI PUSKESMAS KOMBOS KECAMATAN SINGKIL KOTA MANADO - Sisca Solang; Anastance Lohoraung; Atik Purwandari (POLTEKKES KEMENKES MANADO, 2012)
Maternal and perinatal health problems is a national problem that needs to be givenpriority, because it determines the quality of human resources in the generations tocome. Antenatal care is the care given to pregnant women from conception to earlyconfirmation of delivery by first visiting the coverage of the visit of pregnant womenwho first received Antenatal Care services and visits to four, namely coverage of thevisit has obtained the minimum service four visits. This study aimed to identify thefrequency of visits and analyze the relationship of maternal satisfaction with thefrequency of service visits for pregnant women. This research method is a crosssectional analytic approach to the population is the entire third trimester pregnantwomen who visited health centers Antenatal Care in Kombos and the samples takenwere 61 pregnant women. The data was collected using a register then analyzedusing SPSS test. The results obtained in Kombos Health Center suggests thatwomen are satisfied with the services provided by the number of 36 respondents(59%) and the number 25 Dissatisfied respondents (41%) for a good amount offrequency of visits is 22 respondents (36.1%) and frequency of visits is less than 39respondents (63.9%). Chi Square test results using SPSS 16 with p = 0.000 where α= 0.05 (0,000 ˂ 0.05). Conclusion; satisfaction of services rendered affect thefrequency of visits for pregnant women.